Expression of metastasis suppressor BRMS1 in breast cancer cells results in a marked delay in cellular adhesion to matrix. Issue 12 (2nd September 2013) - Khotskaya, Yekaterina B.; Beck, Benjamin H.; Hurst, Douglas R.; Han, Zhenbo; Xia, Weiya; Hung, Mien‐Chie; Welch, Danny R.
Abstract Metastatic dissemination is a multi‐step process that depends on cancer cells' ability to respond to microenvironmental cues by adapting adhesion abilities and undergoing cytoskeletal rearrangement. Breast Cancer Metastasis Suppressor 1 (BRMS1) affects several steps of the metastatic cascade: it decreases survival in circulation, increases susceptibility to anoikis, and reduces capacity to colonize secondary organs. In this report, BRMS1 expression is shown to not significantly alter expression levels of integrin monomers, while time‐lapse and confocal microscopy revealed that BRMS1‐expressing cells exhibited reduced activation of both β1 integrin and focal adhesion kinase, and decreased localization of these molecules to sites of focal adhesions. Short‐term plating of BRMS1‐expressing cells onto collagen or fibronectin markedly decreased cytoskeletal reorganization and formation of cellular adhesion projections. Under 3D culture conditions, BRMS1‐expressing cells remained rounded and failed to reorganize their cytoskeleton and form invasive colonies. Taken together, BRMS1‐expressing breast cancer cells are greatly attenuated in their ability to respond to microenvironment changes. © 2013 Wiley Periodicals, Inc.